Does Sibling Gender Affect Personality Traits? - Bart H.H. Golsteyn; Cécile A. J. Magnée (Institute of Labor Economics (IZA), 2020)
This paper studies whether sibling gender affects personality traits. We use the idea that if parents decide to have a second child, it is random whether they will have a boy or a girl. Therefore, the relationship between the second-born sibling's gender and the first sibling's personality traits is causal. We employ longitudinal data from a large British cohort which is followed from birth onwards. The dataset includes personality traits at age 10 and 16. Our main result is that oldest boys in a household are more agreeable if their next-born sibling is a girl. This effect is robust across age (10 and 16), when controlling for among others family size, and when applying corrections for multiple hypothesis tests. Agreeableness is an important trait in life as it has been shown to correlate positively among others with being employed, having a skilled job, savings, and life satisfaction.
Keywords: I2; J12; J16; J24; 330; sibling gender composition; personality traits